A convenient synthesis of 4-benzyl-2-(2-(4-oxo-2- thioxothiazolidin-5-ylidene)ethyl)-2H-1,4-benzoxazin- 3(4H)-ones and 5-(2-(4-benzyl-3-oxo-3,4-dihydro-2H- 1,4-benzoxazin-2-yl)ethylidene)thiazolidine-2,4-diones - Zidar, Nace (Acta chimica slovenica, 2009)
4-Benzyl-2-(2-(4-oxo-2-thioxothiazolidin-5-ylidene)ethyl)-2H-1,4-benzoxazin-3(4 H)-ones and 5-(2-(4-benzyl-3-oxo- 3,4-dihydro-2H-1,4-benzoxazin-2-yl)ethylidene)thiazolidine-2,4-diones are conveniently prepared from 2-aminophenol and rhodanine or thiazolidine-2,4-dione derivatives using microwave-assisted synthesis
Keywords: analiza; organska kemija; rodanin; sinteza; tiazolidini